From learners to entrepreneurs - Naila Aaijaz; Mohamed Dahlan Ibrahim; Rabiah Bujang (Lap Lambert Academic Publishing, 2013)
This book offers to enlighten its readers on the need to revisit and re-think university education offerings, re-define education strategies and objectives re-structure entrepreneurial education at universities, and re-engineer entrepreneurial churning processes and mechanisms through formal learning. Advisable to be ready by university staff, academic experts, students, researchers, academic curriculum designing professionals of technical, management, entrepreneurship and research related courses, ministry of education and higher education law makers, owners and top management of academic institutions, college, academic and research associations, industry experts, journalists, other media professionals , small & medium enterprise owners (SME's) and entrepreneurs, it will be a treatise for libraries and book publishers, knowledge management archives and data centre world over.